2018
DOI: 10.3390/ijerph15081604
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease, Disability, Psychological Distress and Suicide Ideation among Rural Elderly: Results from a Population Survey in Shandong

Abstract: Objective: Suicide is a major public health and social problem in contemporary societies. Previous studies showed that the older the seniors were, the more likely it was that they would experience disability, chronic disease, or both. The objective of this study was to examine the joint effects of chronic disease and physical disability on suicide ideation while controlling for psychological distress among the rural elderly living in Shandong Province, China. Method: A total of 5514 rural elderly individuals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…The current study found that the prevalence of SI among rural older adults in Shandong Province was 10.6%. This was similar to another survey conducted in rural Shandong (11.0%) [ 12 ]. It was also close to the reported rates in the older US Chinese population (9.4%) [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study found that the prevalence of SI among rural older adults in Shandong Province was 10.6%. This was similar to another survey conducted in rural Shandong (11.0%) [ 12 ]. It was also close to the reported rates in the older US Chinese population (9.4%) [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…The higher the level of psychological distress, the more likely to the older adults suffer from SI. A study has shown that ADL disability promoted SI by increasing psychological distress among Chinese rural older adults [ 12 ]. Our study revealed that psychological distress played the largest mediating role in the association between ADL and SI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also found that a history of chronic disease was associated with suicidal thoughts, which was consistent with other studies carried out in China and in other countries (42,43). A study conducted among 5,514 rural elderly individuals in Shandong province, China, found that chronic disease had both direct and indirect impacts on suicidal ideation (44). Moreover, Handley et al (45) found that within high psychological distress, lower physical functioning significantly increased the likelihood of suicidal ideation, with high distress and low functioning being associated with ideation in 50% of cases through a decision tree analysis.…”
Section: Discussionsupporting
confidence: 93%
“…The legitimacy of conducting comprehensive rehabilitation and activating activities of seniors has been confirmed in many empirical works [3,9,16]. Research conducted by the Zhu team on a population of 5514 people over 60 prove that the leading factors determining the occurrence of affective disorders, especially suicidal thoughts in the seniors' population are limitations in everyday activity and functional ability resulting from experienced chronic diseases [17]. However other studies demonstrate that as a result of a rehabilitation program in elderly people with mild depression, a significant improvement in mental health was achieved -there was a reduction in the severity of depressive symptoms and perceived stress, as well as improved physical fitness [6].…”
Section: Discussionmentioning
confidence: 97%